Dynamic Behavior of Reverse Flow Reactor for Lean Methane Combustion - Budhi, Yogi W.; Effendy, M.; Bindar, Yazid; Subagjo, S. (ITB Journal Publisher, LPPM ITB, 2014)
The stability of reactor operation for catalytic oxidation of lean CH4 has been investigated through modeling and simulation, particularly the influence of switching time and heat extraction on reverse flow reactor (RFR) performance. A mathematical model of the RFR was developed, based on one-dimensional pseudo-homogeneous model for mass and heat balances, incorporating heat loss through the reactor wall. The configuration of the RFR consisted of inert-catalyst-inert, with or without heat extraction that makes it possible to store the energy released by the exothermic reaction of CH4 oxidation. The objective of this study was to investigate the dynamic behavior of the RFR for lean methane oxidation and to find the optimum condition by exploring a stability analysis of the simple reactor. The optimum criteria were defined in terms of CH4 conversion, CH4 slip, and heat accumulation in the RFR. At a switching time of 100 s, the CH4 conversion reached the maximum value, while the CH4 slip attained its minimum value. The RFR could operate autothermally with positive heat accumulation, i.e. 0.02 J/s. The stability of the RFR in terms of heat accumulation was achieved at a switching time of 100 s.